Analysis Poverty of Fishermen's Households in The Coastal Area of Ambulu District, Jember Regency - Afsah Indah Maulidah; Sujarwo; Budi Setiawan (HABITAT, 2022)
This study aims to describe determine the factors that affect the household poverty of the Watu Ulo Sumberejo Village, Ambulu Sub District, Jember  District. The research was conducted in watu ulo in Ambulu Sub District, Jember  District. the selection of the research location was carried out deliberately (Purposive), with the consideration that the village is a coastal village with many fisherman household settlements, most of whom work as fishermen which own a fishing boat smaller or equal to five gross tonnages (GT). The population in this study were all the fisherman household of Watu Ulo in Ambulu Sub District, Jember district, namely 316 Household, with a total sample size of 38 respondents using the Yamane formula. To answer the objective, a binary probit model is used. The results showed that based on the binary probit test, the factors that significantly influenced household poverty of Watu Ulo in Ambulu Sub District, Jember District were the number of household members, education of the head of the household, the catch payment. It is necessary to improve distribution within the government, monitoring, counseling, and the support from the goverment so that the government is right on target. Keywords: household; small; fisherman; poverty; probit